Design and simulation of capacitive mems microphone for fully implantable cochlear implants / Somanaathan Muthusamy - Somanaathan, Muthusamy (2018)
In this work we present the design, Taguchi optimization and simulation of an acoustic sensors array for detecting specific frequencies in a range and allowing their identification from a complex audio signal to develop an application for cochlear implants. The technological development of cochlear implants has enabled patients affected by severe to intense hearing loss to hear sounds and recognize speech in various degree. The sensitivity is obtained when a membrane resonates when stimulated by acoustic wave. In this research sensitivity and linearity of membrane has been improved to overcome the disability of hearing soft and loud sound. The different gap size between the membrane and backplates generates a capacitance change that can pass to an electronic circuit for output signal. The frequency of membrane increases when the spring constant of each membrane increase. In this study, several structures have been studied to optimize the sensitivity and linearity. Based on the results, shortlisted the best performance structures for the Taguchi optimization and Eigen frequency analysis for designated number of arrays. Each array again simulated for identify the sensitivity, linearity and dimension. The best design is being verified from this methodology. This design produces high sensitivity 0.18pF/Pa, linearity 0.0011pF/μm and mechanical sensitivity 35.6μm/Pa compares to existing design. This innovative design can improve current commercial cochlear implant by hearing soft and loud sound without adjusting manually. The life quality of cochlear implant patient is improved by new high sensitive capacitive microphone.